Complete genome sequence of Photobacterium sp. strain J15, isolated from seawater of Southwestern Johor, Malaysia - Roslan, Noordiyanah Nadhirah; Sabri, Suriana; Oslan, Siti Nurbaya; Baharum, Syarul Nataqain; Thean, Chor Leow (American Society for Microbiology, 2016)
Here, we report the genome sequences of Photobacterium sp. strain J15, isolated from seawater in Johor, Malaysia, with the ability to produce lipase and asparaginase. The PacBio genome sequence analysis of Photobacterium sp. strain J15 generated revealed its potential in producing enzymes with different catalytic functions.